The relationship between six minutes walking distance and quality of life in pulmonary tuberculosis sequelae patients - Heni Retnowulan; Deddy Nur Wachid Achadiono; Anggraeni Ayu Rengganis (Faculty of Medicine Universitas Gadjah Mada, 2016)
ABSTRACTBackground: Tuberculosis is an infectious disease that affects the lung and has high incidence. It could leave sequelae in the patient that has been declared cured. Tuberculosis sequelae results in changes of lung function that could lead to deteriorating of functional capacity and quality of life.Aim: The study aim to determine the relationship between functional capacity (6MWD) and quality of life (SGRQ) within pulmonary tuberculosis sequelae patients.Method: This study used cross sectional design and performed on pulmonary tuberculosis sequelae patient in pulmonary clinic of Dr. Sardjito General Hospital and BP4 Yogyakarta. Functional capacity was assessed with six minutes walking distance and assessment of quality of life using SGRQ questionnaire. Distribution of data was tested using the Shapiro-Wilk statistical test. Spearman correlation test and regression test was used to analyze the correlation between 6-minute walking distance test and assessment of quality of life using the SGRQ questionnaire.Result: The 6 minutes walking distance was 257.02±64.56 m. There were significant negative correlation between 6 minutes walking distance and SGRQ score activity domain (r=-.333, p<0.05). The others domains in SGRQ, there were no significant negative correlation at domain symptoms (r-.062), impacts (-.114), and total (-.135).Conclusion: There were negative correlation between the 6 minutes walking distance (6MWD) and SGRQ score. There was significant negative correlation between 6 minutes walking distance (6MWD) and activity domain in the SGRQ score.Keywords: tuberculosis sequelae, functional capacity, 6MWD, quality of life, SGRQ.